GAMBARAN PERAN KADER DALAM PELAKSANAAN PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DI WILAYAH KERJA PUSKESMAS PADURESO KABUPATEN KEBUMEN - Kusumastuti, K; Novyriana, Eka; Utami, Dwi (LPPM STIKES MUHAMMADIYAH GOMBONG, 2015)
Mortality and morbidity is a big problem in a developing country such as Indonesia. Minister of Health in 2007 planned a program of labor Planning and Complications Prevention (Indonesian=P4K) by using stickers as efforts to accelerate the decline in infant mortality rate (IMR) and maternal mortality rate (MMR). By implementation of this Program, there should be a good role of midwives, kader, religious leaders, community leaders, husbands, pregnant women and families.This study is to find out the overview of kader’s role in labor planning program and complication Prevention in Padureso Kebumen.This is a descriptive research using observasional design. There are 37 respondents as the samples research by using simple random sampling. The instruments are questioner and interview.The overview of kader’s role in labor planning program and complication Prevention in Padureso Kebumen is categorized good (43.2%), kader’s role in filling sticker format is categorized bad (27.0%), kader’s role in facilitating the family is categorized good (32.4%), kader’s role in gaining agreement is categorized (54.1%), monitoring result is categorized bad (62.2%), kader’s role in evaluating result is categorized bad (67.6%), and kader’s role in performing report is categorized bad (59%). Keywords: kader’s role, labor planning program and complication Prevention implementation